(untitled) (Global Journal of Cultural Studies, 2024)
Material culture encompasses more than objects; it represents the dynamic interactions between people and artifacts, embedding cultural practices, values, and social structures within tangible forms. Rooted primarily in archaeology and anthropology, Material Culture is closely associated with technology, understood as the processes and systems underlying artifact creation and use. This relationship underscores technology´s role as a cultural process, involving the organization of knowledge, practices, and social interactions. While Material Culture focuses on artifacts as cultural symbols, technology explores their production processes. Holistic technologies, characterized by individual artisans’ control over production, contrast with prescriptive technologies, which employ segmented labour, reflecting advancements in social and economic organization. The distinction highlights the interplay between technological practices and societal dynamics. Anthropological studies demonstrate how cultural factors influence technological practices, including gendered roles in the creation of artifacts. Artifacts encode information, not only serving utilitarian purposes but also acting as media for memory, identity, and power relations. The meanings embedded in the objects often transcend their materiality, reflecting complex social and cultural ideologies. By bridging the tangible and intangible, Material Culture provides a critical framework for understanding the relationship between culture, technology, and society. This perspective reveals how technological processes shape human experience and contribute to the materialization of cultural values and beliefs, offering valuable insights into the evolution of social systems and identities.